Dilated Cardiomyopathy From Genetics to Clinical Management - Sinagra, Gianfranco; Merlo, Marco; Pinamonti, Bruno (Springer Nature, 2019)
This open access book presents a comprehensive overview of dilated cardiomyopathy, providing readers with practical guidelines for its clinical management. The first part of the book analyzes in detail the disease's pathophysiology, its diagnostic work up as well as the prognostic stratification, and illustrates the role of genetics and gene-environment interaction. The second part presents current and future treatment options, highlighting the importance of long-term and individualized treatments and follow-up. Furthermore, it discusses open issues, such as the apparent healing phenomenon, the early prognosis of arrhythmic events or the use of genetic testing in clinical practice. Offering a multidisciplinary approach for optimizing the clinical management of DCM, this book is an invaluable aid not only for the clinical cardiologists, but for all physicians involved in the care of this challenging disease.